2003
DOI: 10.1017/s0021859603002958
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance of white clover varieties grown with perennial ryegrass under rotational grazing by sheep with different nitrogen applications

Abstract: SU MMARYThree experiments were carried out to investigate the dry matter production of nine white clover (Trifolium repens L.) varieties grown with the same variety of perennial ryegrass (Lolium perenne L.) and subjected to rotational grazing by sheep over a period of 10 years. The experiments differed only in the nitrogen fertilizer added : no nitrogen, 100 kg/ha per year and 200 kg/ha per year. Dry matter (DM) yields of white clover and perennial ryegrass components of the sward were recorded at approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Harris et al (1999) reported that deferred grazing of pasture increased clover proportion in pasture in subsequent seasons. Williams et al (2003b) reported that under rotational stocking with sheep, white clover can give reliably high yield over a 10-yr period. Brink and Pederson (1993) made several important observations on white clover response to grazing method.…”
Section: Growth and Persistencementioning
confidence: 99%
“…Harris et al (1999) reported that deferred grazing of pasture increased clover proportion in pasture in subsequent seasons. Williams et al (2003b) reported that under rotational stocking with sheep, white clover can give reliably high yield over a 10-yr period. Brink and Pederson (1993) made several important observations on white clover response to grazing method.…”
Section: Growth and Persistencementioning
confidence: 99%
“…Nitrogen fertilization, which tends to enhance both total forage yield and grass competitive ability, may have a major impact on white clover–grass dynamics. Fertilization rates of c .100 kg ha −1 per year allow for a compromise between high forage yield and allowing sufficient clover content in white clover–perennial ryegrass mixtures in the UK (Frame and Boyd, 1987; Williams et al. , 2003) and in New Zealand (Clark and Harris, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of results from long‐term experiments have been published (e.g. Williams et al. , 2003), but in most cases their relevance has been restricted to a specific management system.…”
Section: Introductionmentioning
confidence: 99%